Dominant role of eddies and filaments in the offshore transport of carbon and nutrients in the California Current System. Issue 8 (3rd August 2015) - Nagai, Takeyoshi; Gruber, Nicolas; Frenzel, Hartmut; Lachkar, Zouhair; McWilliams, James C.; Plattner, Gian‐Kasper
Abstract The coastal upwelling region of the California Current System (CalCS) is a well‐known site of high productivity and lateral export of nutrients and organic matter, yet neither the magnitude nor the governing processes of this offshore transport are well quantified. Here we address this gap using a high‐resolution (5 km) coupled physical‐biogeochemical numerical simulation (ROMS). The results reveal (i) that the offshore transport is a very substantial component of any material budget in this region, (ii) that it reaches more than 800 km into the offshore domain, and (iii) that this transport is largely controlled by mesoscale processes, involving filaments and westward propagating eddies. The process starts in the nearshore areas, where nutrient and organic matter‐rich upwelled waters pushed offshore by Ekman transport are subducted at the sharp lateral density gradients of upwelling fronts and filaments located at ∼25–100 km from the coast. The filaments are very effective in transporting the subducted material further offshore until they form eddies at their tips at about 100–200 km from the shore. The cyclonic eddies tend to trap the cold, nutrient, and organic matter‐rich waters of the filaments, whereas the anticyclones formed nearby encapsulate the low nutrient and low organic matter waters around the filament. After their detachment, both types of eddies propagate further in offshore direction, with a speed similar to that of the first baroclinic mode Rossby waves, providing the key mechanism for long‐range transport of nitrate and organic matter from the coast deep into the offshore environment.